Answer:
g(-2) = -2
g(-0.5) = -1
g(1) = 1
Step-by-step explanation:
Let us plot g(x):
Let us first evaluate g(-2). This means we are to find the value of g(x) when x = -2.
As can be seen from the above plot, when x = -2, g(x) = -2; Therefore,
![\boxed{g(-2)=-2.}](https://img.qammunity.org/2023/formulas/mathematics/college/rmap1jpgdz2vyyd4nidpnu3fni5hjcqh7i.png)
To evaluate g(-0.5), we find the value of g(x) when x = -0.5.
From the plot we can see that when x = -0.5, g(x) = -1; therefore,
![\boxed{g(-0.5)=-1.}](https://img.qammunity.org/2023/formulas/mathematics/college/5o9b9s7bwd0m4tp2ol0zrwsgoyhj4rz314.png)
To evaluate g(1), we find the value of g(x) when x = 1.
From the plot we can see that when x =1, g(x) = 1; therefore,
![\boxed{g(1)=1.}](https://img.qammunity.org/2023/formulas/mathematics/college/kp0ozg0bpxnypl9c2lmgmf62d1z1b4u70g.png)
which is our answer!
Hence, to summerise
g(-2) = -2
g(-0.5) = -1
g(1) = 1